ATHLETIC PUBALGIA – A DIAGNOSTIC AND THERAPEUTIC CHALLENGE IN CLINICAL PRACTICE - Sobczyńska, Kamila; Judzińska, Alicja; Terbosh, Magda; Piech, Bartosz; Osipowska, Julia; Ignarska, Justyna; Kubicz Mzabi, Sabina; Dubaj, Magdalena; Trojanowska, Emilia; Kwolek, Marlena (International Journal of Innovative Technologies in Social Science, 2026)
Introduction: Athletic pubalgia is a complex medical issue that affects athletes like footballers or  hockey players. Chronic groin pain is caused by overuse injuries of the musculotendinous structures around the pubic symphysis. This review article aims to present the current knowledge on athletic pubalgia, including pathophysiology, epidemiology, diagnostic approaches and treatment strategies.Methods: This article is based on 30 scientific publications from PubMed, Journal of Education, Health and Sport and Google Scholar. In this review we pay attention to the latest information about risk factors, diagnostic methods, significant symptoms and management strategies.Results: Athletic pubalgia usually affects male professional athletes like football and hockey players. Groin pain coexisting with specific exercises and movements is the most common symptom. To make a correct diagnosis, the clinical picture, imaging studies, and clinical tests must be considered. First-line treatment is conservative therapy, which is sufficient in most cases. Further treatment includes special rehabilitation programs combined with surgical treatment, most often using endoscopic methods.Conclusions: Athletic pubalgia is a condition that has long been known to clinicians in the professional and recreational sport population. However, it requires detailed diagnostics, including specially selected tests performed during a physical examination and imaging techniques—particularly MRI—performed by experienced specialists. Available treatment methods, tailored to the severity of the condition, allow the vast majority of patients to fully return to sport.